Molecular and serological detection of Ehrlichia spp. in cats on São Luís Island, Maranhão, Brazil - Braga, Maria do Socorro Costa de Oliveira; André, Marcos Rogério [UNESP]; Freschi, Carla Roberta [UNESP]; Teixeira, Márcia Cristina Alves [UNESP]; Machado, Rosangela Zacarias [UNESP] (Colégio Brasileiro de Parasitologia Veterinária, 2012)
Erliquiose é uma enfermidade transmitida por carrapatos que afeta seres humanos e animais. Os poucos relatos de erliquiose em gatos, no Brasil, são baseados na observação de mórulas em leucócitos e, mais recentemente, na detecção molecular de Ehrlichia sp. Neste estudo, foi avaliada a ocorrência de Ehrlichia sp. no sangue de 200 gatos de São Luís, Maranhão. Dos 200 animais testados, 11 (5,5%) foram soropositivos para Ehrlichia sp. e dois (1%) foram positivos na PCR para Ehrlichia spp. O alinhamento de sequências de DNA baseado no gene 16S rRNA foi conduzido para estabelecer a identidade da espécie de parasito que infectou estes animais. Um gato apresentou infecção por uma espécie de Ehrlichia sp. com 98% de identidade com E. canis; e outro mostrou-se infectado por Ehrlichia sp. com 97% de identidade com E. chaffeensis. Este estudo traz a primeira detecção molecular de Ehrlichia sp. em gatos de São Luís, Maranhão.

Ehrlichiosis is a tick-borne disease that affects both humans and animals. The few existing reports on ehrlichiosis in Brazilian cats have been based on observation of morulae in leukocytes and, more recently, on molecular detection of Ehrlichia sp. In this study, we assessed occurrences of Ehrlichia sp. in the blood of 200 domestic cats in São Luís, Maranhão. of the 200 animals tested, 11 (5.5%) were seropositive for Ehrlichia sp. and two (1%) were positive for Ehrlichia sp. in PCR. We also performed DNA sequence alignment to establish the identity of the parasite species infecting these animals, using the gene 16S rRNA. One cat presented infection with Ehrlichia sp. with 98% identity with E. canis, and another cat infected with Ehrlichia sp. showed 97% identity with E. chaffeensis. This is the first study on molecular detection of Ehrlichia sp. among domestic cats in São Luís, Maranhão.
Detecção molecular e sorológica de Ehrlichia spp. em gatos da ilha de São Luís, Maranhão, Brasil
Keywords: Cat; Ehrlichia sp.; Serology; PCR; Brazil; Gatos; Ehrlichia sp.; Sorologia; PCR; Brasil